Proud Mary [videorecording (DVD)] - Henson, Taraji P.; Brown, Billy (Actor); Winston, Jahi Di'allo (Sony Pictures Home Entertainment, 2018)
Mary is a hitwoman working for an organized crime family in Boston. Her life is completely turned around when she meets a young boy whose path she crosses when a professional hit goes awry.